Doping type single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability and preparation method thereof
Through the preparation of doped single crystal sodium ion battery positive electrode material, the problems of low working voltage and poor cycle stability of existing NaNiFeMn layered oxide materials are solved, and a positive electrode material with high specific capacity and long cycle stability is achieved, which is suitable for commercial applications of sodium ion batteries.
Patent Information
- Application Number
- CN202411970391.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
The existing NaNiFeMn layered oxide material as the positive electrode material of sodium ion battery has a low operating voltage and poor cycling stability under high voltage conditions, which limits its use in commercial applications.
The positive electrode material of doped single crystal sodium ion battery is adopted, with a specific structure of NaNixFeyMnzO2. By controlling the content and types of doped elements and combining with high temperature sintering method, a positive electrode material with high specific capacity and long cycle stability is prepared.
High operating voltage (>3.15V) in the 2-4.2V voltage range and excellent multi-cycle electrochemical stability are achieved, which significantly improves the energy density and cycle stability of sodium ion batteries.
Smart Images

Figure CN119710928A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials for sodium ion batteries, and in particular to a doped single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability and a preparation method thereof. Background Art
[0002] In the field of energy storage in recent years, with the rapid development of renewable energy and the increasing demand for electric vehicles, the research and innovation of battery technology has received widespread attention. As a potential alternative to lithium-ion batteries, sodium-ion batteries have gradually become a research hotspot due to their abundant resources, low cost, and environmental friendliness. However, sodium-ion batteries still face many challenges in terms of high specific capacity and long cycle stability, especially the performance improvement and optimization of cathode materials.
[0003] In order to improve the energy density and cycle stability of sodium-ion batteries, researchers have tried a variety of sodium-ion battery cathode materials, including layered oxides, phosphates, sulfides, etc. Among various cathode materials, layered oxide cathode materials have been widely studied due to their high theoretical capacity and simple synthesis methods. NaNiFeMn layered oxide materials have the characteristics of high capacity and low cost. However, NaNiFeMn layered oxide materials have low operating voltage and are prone to many adverse reactions and phenomena during their cycle, such as structural instability and surface degradation, especially under high voltage, which hinders their commercial application. Therefore, the development of a single crystal sodium-ion battery cathode material with good long-cycle stability under high voltage is the key to the further development of sodium-ion battery technology. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a doped single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability and a preparation method thereof, so as to solve the problems of low operating voltage and poor cycle stability when the existing NaNiFeMn layered oxide material is used as a positive electrode material for sodium ion batteries, especially under high pressure conditions, etc.
[0005] The technical solution of the present invention to solve the above technical problems is as follows:
[0006] A doped single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability. The positive electrode material is a single crystal with an O3 type structure and a general structural formula of NaNi x Fe y Mn z O 2 , where x=0.2-0.6, y=0.1-0.3, z=0.2-0.6.
[0007] Furthermore, the general structural formula of the cathode material is NaNi 0.4Fe 0.2 Mn 0.4 O 2 .
[0008] The method for preparing the above-mentioned doped single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability comprises the following steps:
[0009] The precursor material, sodium carbonate and dopant are mixed and ball-milled, then sintered at high temperature, and finally cooled to room temperature, crushed and ground to obtain the product.
[0010] Furthermore, the precursor material is Ni 0.2-0.6 Fe 0.1-0.3 Mn 0.2-0.6 (OH) 2 or Ni 0.2-0.6 Fe 0.1-0.3 Mn 0.2-0.6 (CO) 3 .
[0011] Preferably, the precursor material is Ni 0.4 Fe 0.2 Mn 0.4 (OH) 2 or Ni 0.4 Fe 0.2 Mn 0.4 (CO) 3 .
[0012] Furthermore, the molar ratio of the precursor material to sodium carbonate is 1:1.05-1.5.
[0013] Furthermore, the dopant includes at least one of magnesium oxide, titanium dioxide, lithium carbonate, zinc oxide and copper oxide, and the molar ratio of the precursor to the dopant is 1:0.002-0.1.
[0014] Furthermore, the ball milling time is 3-20 hours, and the ball milling speed is 100-1000 rpm.
[0015] Preferably, the ball milling time is 4-10 h, and the ball milling speed is 300-700 rpm.
[0016] Furthermore, the high temperature sintering temperature is 700-1200° C., the heating rate is 2-8° C. / min, and the time is 5-20 h.
[0017] Further, when the molar ratio of the precursor material to sodium carbonate is 1:1.05, the high temperature sintering temperature is 700-1000°C, the heating rate is 2-8°C / min, and the time is 5-15h;
[0018] When the molar ratio of the precursor material to sodium carbonate is 1:1.15, the high-temperature sintering temperature is 1000-1200°C, the heating rate is 2-8°C / min, and the time is 10-20h.
[0019] Furthermore, the particle size of the positive electrode material obtained after crushing and grinding is 2-8 μm.
[0020] The present invention has the following beneficial effects:
[0021] The present invention provides a doped single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability and a preparation method thereof, wherein the average discharge voltage of the positive electrode material is greater than 3.15V, the specific capacity in the voltage range of 2-4.2V is greater than 150mAh / g, and the positive electrode material has excellent electrochemical stability for multiple cycles in the voltage range of 2-4.2V. The present invention successfully solves the problems of low operating voltage and poor long cycle stability of existing sodium ion battery positive electrode materials under high voltage by controlling the content and type of doping elements, high temperature sintering temperature and sintering time, and has high preparation efficiency, low cost and broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 XRD spectrum of the positive electrode material obtained in Example 1;
[0023] Figure 2 This is a scanning electron microscope image of the positive electrode material obtained in Example 1;
[0024] Figure 3 The discharge curve of the sodium ion secondary battery in the voltage range of 2-4.2V obtained in Example 1;
[0025] Figure 4 This is a long cycle performance diagram of the sodium ion secondary battery obtained in Example 1 at a voltage range of 2-4.2V and a rate of 1C;
[0026] Figure 5 XRD spectrum of the positive electrode material obtained in Example 2;
[0027] Figure 6 This is a scanning electron microscope image of the positive electrode material obtained in Example 2;
[0028] Figure 7 The discharge curve diagram of the sodium ion secondary battery in the voltage range of 2-4.2V obtained in Example 2;
[0029] Figure 8 This is a long cycle performance diagram of the sodium ion secondary battery obtained in Example 2 at a voltage range of 2-4.2V and a rate of 1C;
[0030] Fig. 9 This is the XRD spectrum of the positive electrode material obtained in Example 3;
[0031] Fig.10 This is a scanning electron microscope image of the positive electrode material obtained in Example 3;
[0032] Fig.11 The discharge curve of the sodium ion secondary battery in the voltage range of 2-4.2V obtained in Example 3;
[0033] Fig.12 This is a long cycle performance diagram of the sodium ion secondary battery obtained in Example 3 at a voltage range of 2-4.2V and a rate of 1C. DETAILED DESCRIPTION
[0034] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0035] Embodiment 1:
[0036] A method for preparing a doped single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability comprises the following steps:
[0037] First weigh the chemical formula Ni 0.4 Fe 0.2 Mn 0.4 (OH) 2 The hydroxide is used as a precursor, and is mixed with sodium carbonate (the molar ratio of the precursor to sodium carbonate is 1:1.15), nano-copper oxide (the molar ratio of the precursor to nano-copper oxide is 1:0.005), nano-titanium dioxide (the molar ratio of the precursor to nano-titanium dioxide is 1:0.005) and lithium carbonate (the molar ratio of the precursor to lithium carbonate is 1:0.005) and placed in a ball mill, and ball milled at a speed of 500 rpm for 6 hours; then the obtained mixed powder is transferred to a sagger, heated to 1000°C at a heating rate of 3°C / min, and sintered at a high temperature for 15 hours; finally, it is cooled to room temperature, crushed and ground to obtain a powder with a particle size of about 6 μm.
[0038] The positive electrode material powder prepared in this embodiment was subjected to X-ray diffraction test and scanning electron microscope test. The experimental results are as follows: Figure 1 and Figure 2 shown.
[0039] like Figure 1 As shown, the positive electrode material powder prepared in this embodiment is an O3 type pure phase structure; Figure 2 As shown, the positive electrode material prepared in this embodiment is a single crystal particle with a particle size of about 6 μm.
[0040] The positive electrode material prepared in this example is mixed with a conductive material (Super P) and a binder (PVDF) in a mass ratio of 7:2:1 to form a uniform slurry, which is then evenly coated on an aluminum foil to prepare a positive electrode sheet for a sodium ion secondary battery. The negative electrode is a metal sodium sheet, the diaphragm is a glass fiber membrane, and the electrolyte is NaClO 4 The solution was assembled into a battery and the charge and discharge performance was tested using a Blue Electric charge and discharge tester. The battery charge and discharge test was conducted under the following conditions: the charge and discharge voltage range was 2.0V to 4.2V. First, an activation cycle was performed at a 0.1C rate, and then a 100-cycle long cycle test was performed at a 1C rate to evaluate the cycle stability and long-cycle performance of the positive electrode material. The experimental results are shown in Figure 3 and Figure 4 shown.
[0041] like Figure 3 The charge and discharge curve of the sodium ion secondary battery corresponding to this embodiment is shown. The horizontal axis in the figure represents the capacity of the battery, in units of mAh / g, and the vertical axis represents the voltage of the battery, in units of V. It can be seen from the charge and discharge curve that the 0.1C discharge capacity is 149.43mAh / g, the first efficiency reaches 97.84%, and the average discharge voltage is 3.23V, which is significantly higher than the common single crystal material working voltage of 3.0V on the market.
[0042] like Figure 4 The long cycle performance of the sodium ion secondary battery corresponding to this embodiment at 1C is shown. The results show that the capacity reaches 123.08 mAh / g after 100 cycles at 1C rate, and the capacity retention rate reaches 89.34%.
[0043] Embodiment 2:
[0044] A method for preparing a doped single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability comprises the following steps:
[0045] First weigh the chemical formula Ni 0.4 Fe 0.2 Mn 0.4 (OH) 2 The hydroxide is used as a precursor, mixed with sodium carbonate (the molar ratio of the precursor to sodium carbonate is 1:1.05), nano zinc oxide (the molar ratio of the precursor to nano zinc oxide is 1:0.005) and nano titanium dioxide (the molar ratio of the precursor to nano titanium dioxide is 1:0.005) and placed in a ball mill, and ball milled at 500 rpm for 4 hours; then the obtained uniformly mixed powder is transferred to a sagger, heated to 950°C at a heating rate of 3°C / min and sintered at a high temperature for 15 hours; finally, it is cooled to room temperature, crushed and ground to obtain a powder with a particle size of about 3μm, and the product is obtained.
[0046] The positive electrode material powder prepared in this embodiment was subjected to X-ray diffraction test and scanning electron microscope test. The experimental results are as follows: Figure 5 and Figure 6 shown.
[0047] like Figure 5 As shown, the positive electrode material powder prepared in this embodiment is an O3 type pure phase structure; Figure 6 As shown, the positive electrode material prepared in this embodiment is a single crystal particle with a particle size of about 3 μm.
[0048] The positive electrode material prepared in this example is mixed with a conductive material (Super P) and a binder (PVDF) in a mass ratio of 7:2:1 to form a uniform slurry, which is then evenly coated on an aluminum foil to prepare a positive electrode sheet for a sodium ion secondary battery. The negative electrode is a metal sodium sheet, the diaphragm is a glass fiber membrane, and the electrolyte is NaClO 4 The solution was assembled into a battery and the charge and discharge performance was tested using a Blue Electric charge and discharge tester. The battery charge and discharge test was conducted under the following conditions: the charge and discharge voltage range was 2.0V to 4.2V. First, an activation cycle was performed at a 0.1C rate, and then a 100-cycle long cycle test was performed at a 1C rate to evaluate the cycle stability and long-cycle performance of the positive electrode material. The experimental results are shown in Figure 7 and Figure 8 shown.
[0049] like Figure 7 The charge and discharge curve of the sodium ion secondary battery corresponding to this embodiment is shown. The horizontal axis in the figure represents the capacity of the battery, in units of mAh / g, and the vertical axis represents the voltage of the battery, in units of V. It can be seen from the charge and discharge curve that the 0.1C discharge capacity is 142.21mAh / g, the first efficiency reaches 97.84%, and the average discharge voltage is 3.17V, which is significantly higher than the common single crystal material working voltage of 3.0V on the market.
[0050] like Figure 8 The long cycle performance of the sodium ion secondary battery corresponding to this embodiment at 1C is shown. The results show that the capacity reaches 76.83 mAh / g after 100 cycles at a rate of 1C, and the capacity retention rate reaches 68.13%.
[0051] Embodiment 3:
[0052] A method for preparing a doped single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability comprises the following steps:
[0053] First weigh the chemical formula Ni 0.4 Fe 0.2 Mn 0.4 (OH) 2The hydroxide is used as a precursor, mixed with sodium carbonate (the molar ratio of the precursor to sodium carbonate is 1:1.05), lithium carbonate (the molar ratio of the precursor to lithium carbonate is 1:0.02) and nano-titanium dioxide (the molar ratio of the precursor to nano-titanium dioxide is 1:0.02) and placed in a ball mill, and ball milled at 400 rpm for 6 hours; then the obtained mixed powder is transferred to a sagger, heated to 950°C at a heating rate of 5°C / min, and sintered at a high temperature for 12 hours; finally, it is cooled to room temperature, crushed and ground to obtain a powder with a particle size of about 2μm.
[0054] The positive electrode material powder prepared in this embodiment was subjected to X-ray diffraction test and scanning electron microscope test. The experimental results are as follows: Fig. 9 and Fig.10 shown.
[0055] like Fig. 9 As shown, the positive electrode material powder prepared in this embodiment is an O3 type pure phase structure; Fig.10 As shown, the positive electrode material prepared in this embodiment is a single crystal particle with a particle size of about 2 μm.
[0056] The positive electrode material prepared in this example is mixed with a conductive material (Super P) and a binder (PVDF) in a mass ratio of 7:2:1 to form a uniform slurry, which is then evenly coated on an aluminum foil to prepare a positive electrode sheet for a sodium ion secondary battery. The negative electrode is a metal sodium sheet, the diaphragm is a glass fiber membrane, and the electrolyte is NaClO 4 The solution was assembled into a battery and the charge and discharge performance was tested using a Blue Electric charge and discharge tester. The battery charge and discharge test was conducted under the following conditions: the charge and discharge voltage range was 2.0V to 4.2V. First, an activation cycle was performed at a 0.1C rate, and then a 100-cycle long cycle test was performed at a 1C rate to evaluate the cycle stability and long-cycle performance of the positive electrode material. The experimental results are shown in Fig.11 and Fig.12 shown.
[0057] like Fig.11 The charge and discharge curve of the sodium ion secondary battery corresponding to this embodiment is shown. The horizontal axis in the figure represents the capacity of the battery, in units of mAh / g, and the vertical axis represents the voltage of the battery, in units of V. It can be seen from the charge and discharge curve that the 0.1C discharge capacity is 152.80mAh / g, the first efficiency reaches 89.32%, and the average discharge voltage is 3.20V, which is significantly higher than the common single crystal material working voltage of 3.0V on the market.
[0058] like Fig.12 The long cycle performance of the sodium ion secondary battery corresponding to this embodiment at 1C is shown. The results show that the capacity reaches 123.93 mAh / g after 100 cycles at 1C rate, and the capacity retention rate reaches 87.90%.
[0059] In summary, the present invention successfully prepares single crystal positive electrode materials by a simple high temperature sintering method, and obtains positive electrode materials with high working voltage (>3.15V) and excellent performance in the voltage range of 2-4.2V by doping with multiple elements in different types and proportions. The preparation method of the present invention is simple and has excellent performance, which meets the market demand for simplified production process and reliable performance, and has wide application potential.
[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A doped single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability, characterized in that: The positive electrode material is a single crystal with an O3 structure and a general structural formula of NaNi x Fe y Mn z O2, in the formula, x=0.2-0.6, y=0.1-0.3, z=0.2-0.
6.
2. The doped single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability according to claim 1, characterized in that: The general structural formula of the positive electrode material is NaNi 0.4 Fe 0.2 Mn 0.4 O2.
3. The method for preparing the doped single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability according to claim 1 or 2, characterized in that: The following steps are involved: The precursor material, sodium carbonate and dopant are mixed and ball-milled, then sintered at high temperature, and finally cooled to room temperature, crushed and ground to obtain the product.
4. The method for preparing a doped single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability according to claim 3, characterized in that: The precursor material is Ni 0.2-0.6 Fe 0.1-0.3 Mn 0.2-0.6 (OH)2 or Ni 0.2-0.6 Fe 0.1- 0.3 Mn 0.2-0.6 (CO)3.
5. The method for preparing a doped single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability according to claim 3, characterized in that: The molar ratio of the precursor material to sodium carbonate is 1:1.05-1.
5.
6. The method for preparing a doped single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability according to claim 3, characterized in that: The dopant includes at least one of magnesium oxide, titanium dioxide, lithium carbonate, zinc oxide and copper oxide, and the molar ratio of the precursor to the dopant is 1:0.002-0.
1.
7. The method for preparing a doped single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability according to claim 3, characterized in that: The ball milling time is 3-20 hours, and the ball milling speed is 100-1000 rpm.
8. The method for preparing a doped single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability according to claim 3, characterized in that: The high temperature sintering temperature is 700-1200° C., the heating rate is 2-8° C. / min, and the time is 5-20 hours.
9. The method for preparing a doped single crystal sodium ion battery positive electrode material with high specific capacity and long cycle stability according to claim 3, characterized in that: The particle size of the positive electrode material obtained after the crushing and grinding is 2-8 μm.